Corpus callosum infarction: a case report - Almushayti, Ziyad (International Journal of Advances in Medicine, 2020)
Infarctions of corpus callosal are rare due to an abundant collateral blood supply. Few case reports published in the literature regarding the corpus callosum infarction. We present a case of corpus callosum infarction in a 66-year-old man with a history of diabetes mellitus, hypertension, and coronary artery disease who presented to the emergency room with left lower limb weakness. Diagnosed was made based on magnetic resonance imaging and treated conservatively.